If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 14 = 4x + 94 Reorder the terms: 14 + 8x = 4x + 94 Reorder the terms: 14 + 8x = 94 + 4x Solving 14 + 8x = 94 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 14 + 8x + -4x = 94 + 4x + -4x Combine like terms: 8x + -4x = 4x 14 + 4x = 94 + 4x + -4x Combine like terms: 4x + -4x = 0 14 + 4x = 94 + 0 14 + 4x = 94 Add '-14' to each side of the equation. 14 + -14 + 4x = 94 + -14 Combine like terms: 14 + -14 = 0 0 + 4x = 94 + -14 4x = 94 + -14 Combine like terms: 94 + -14 = 80 4x = 80 Divide each side by '4'. x = 20 Simplifying x = 20
| 49-2x=7x+12 | | 9-8x=99-43x | | 5-x=4x+40 | | 8x-4=5x+32 | | 5x-7=-27 | | 5x+7=28-2x | | 7x=3x+32 | | 5x-2=30 | | -6y^2+11y-10=0 | | -4+3q=22 | | 2p-6=22 | | 2p+3=22 | | z^2+98z-64=0 | | x^2+98z-64=0 | | x^2+98x-64=0 | | x^2+5x-64=0 | | x^2+5x+66=0 | | 12a-24=10a+16 | | 3a-6=6a+12 | | 3a-4=6a+12 | | 3a-4=12a+12 | | 3a-12=12a+12 | | 4a-12=12a+12 | | 4a-12=15a+12 | | 4a-12=5a+12 | | 4a-12=10a+12 | | 4a-6=10a+12 | | 4a-6=10a+8 | | 49m^2-16=0 | | jk^2-9j=0 | | 4x-3(x-2)=2(x-1) | | 8j^2-32=0 |